Synthesis of Vanadium‐Incorporated, Polyoxometalate‐Based Open Frameworks and Their Applications for Cathode‐Active Materials. Issue 8 (22nd February 2016) - Zhang, Zhenxin; Yoshikawa, Hirofumi; Zhang, Zhongyue; Murayama, Toru; Sadakane, Masahiro; Inoue, Yasunori; Ueda, Wataru; Awaga, Kunio; Hara, Michikazu
Abstract: The tuning of the chemical composition of polyoxometalate (POM)‐based open framework materials with the same structure, leading to a property change of the materials, is interesting. Here, we report the synthesis of a series of vanadium‐incorporated, ϵ‐Keggin polyoxometalate‐based open framework materials by using a hydrothermal method. The resulting materials were characterized by powder X‐ray diffraction, FTIR spectroscopy, scanning electron microscopy, energy dispersive X‐ray spectroscopy, X‐ray photoelectron spectroscopy, and elemental analysis. Our results indicate that V is successfully incorporated into the frameworks of the materials. The introduced amount of V can be adjusted by controlling the addition of the precursor V compounds. The performances of these materials as cathode materials for Li‐ion batteries have been tested. Incorporation of V can improve the cycle performance. After the 20th cycle of the charge–discharge process, the materials were transformed to the Li2 MoO4 phase. Abstract : Vanadium‐incorporated crystalline polyoxometalate (POM)‐based microporous materials were synthesized and characterized. The amount of V in the materials can be tuned. Incorporation of V affected the properties of the materials. The materials were applied as cathodes for Li‐ion batteries.